Optimization of Unmanned Aerial Vehicle (UAV) Development in the Defense Industry Related to Future Defense and Security Needs - Nanto Nurhuda; Syaiful Anwar; Rizerius Eko Hs (Budapest International Research and Critics University, 2022)
Increasingly sophisticated technological innovations encourage Indonesia to continue to modernize defense equipment and all things that support military activities. One of them is ownership of unmanned aircraft (PTTA) or drones. This unmanned aircraft in the military world is called the Unmanned Aerial Vehicle (UAV) which functions as an air reconnaissance machine as well as a weapon. This article discusses in detail the UAV regulations and their development agencies in Indonesia and the future needs of the Defense and Security Agency by using a descriptive qualitative approach. UAV technology can be used for environmental and security monitoring, weather monitoring, meteorological research, agriculture, mineral exploration, and mining even for military purposes. In Indonesia, the development of UAVs must be optimized by utilizing the Defense Industry that is owned regarding the needs of defense and security tools in the future.